A constituição do profissionalismo docente e suas interfaces com o exercício da docência no ensino superior - Ramirez, Vera Lúcia (2011)
This quanti-qualititative case study investigates the perception of professors who teach clases in the bachelor s undergraduate degree programs offered at Centro Universitário La Salle about the constitution of their teaching professionalism and about the existing interfaces with the teaching practice. The theoretical reference is based on authors who discuss the constitution of teaching professionalism, initial and continuing training, and the demands of Higher Education in contemporaneity, Nóvoa, Pimenta, Pimenta and Anastasiou, Tardif and Perrenoud. The empirical field of this study was Unilasalle/Canoas, located in the metropolitan area of Porto Alegre, in Rio Grande do Sul. The participants were professors of the bachelor s undergraduate degree programs offered by Unilasalle who teach 16 hours a week or more and have been working in the institution for at least 2 years. Data were collected in two different moments: firstly, 74 professors of 23 bachelor s degree programs answered a questionnaire with free-response thematic questions, analyzed using Descriptive Statistics. Secondly, 8 professors responded a semi-structured interview, analysed with Content Analysis Technique, with four a priori categories.Y comment that, in general, a) there are few researches about training of teachers who work in bachelor s degree programs, it is necessary invest in this area of investigation; b) the results show that there is consensus among these professors that in the bachelor s programs the importance is given to technical and scientific training, professors with this initial training lack didactic and pedagogical knowledge; c) the professors interviewed are unanimous in emphasizing that continuing education is fundamental in the teacher training process. Considering that case studies do not aim to generalize their findings, I expect the results collected in this investigation contribute to the excellence in teaching and learning in Higher Education, indicating some subsidies to (re)think continuing training processes and practices for educators.